Cooperative Binding of Metal Cations to a Spiropyran‐Conjugated Calix[4]arene. Issue 12 (27th April 2017) - Lee, Minhe; Cho, Daeheum; Kim, Inwon; Lee, Juhyen; Lee, Jin Yong; Satheeshkumar, Chinnadurai; Song, Changsik
Abstract: Cooperative binding occurs frequently in biological systems, but is less exploited in synthetic receptor molecules. We synthesized a bis(spiropyran)‐conjugated calix[4]arene (bSPTC ) through a 1, 2, 3‐triazole linker and found cooperativity in bindings of a series of divalent metal cations (Ca 2+, Mg 2+, Cd 2+, Co 2+, Fe 2+, Hg 2+, Ni 2+, and Zn 2+ ). UV‐vis absorption spectroscopy and principle component analysis were used to differentiate the recognized metal cations. The binding stoichiometry was determined by various continuation methods, which indicated thatbSPTC has two binding ratios, 1:1 for Zn 2+ and 1:2 for all other metal cations. Importantly, positive cooperativity was suggested for the 1:2 stoichiometry ofbSPTC to Mg 2+ ions from the sigmoidal saturation curve and Hill equation analysis. Density functional theory (DFT) calculations imply that the first binding of Mg 2+ to one spiropyran destabilizes the second spiropyran, which facilitates binding of a second Mg 2+ . Abstract : Cooperative binding occurs frequently in biological systems, but is less exploited in synthetic receptor molecules. We synthesized a bis(spiropyran)‐conjugated calix[4]arene through 1, 2, 3‐triazole linker and found cooperativity in bindings of a series of divalent metal cations. DFT calculations imply that the first binding of M 2+ to one spiropyran destabilizes the second spiropyran, which facilitates binding of a second M 2+ .